2012
DOI: 10.1038/ajg.2012.54
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immune Cell Numbers and Visceral Sensitivity in Patients With Irritable Bowel Syndrome: Is There Any Relationship?

Abstract: Although the number of mast cells, macrophages, T cells, and λFLC-positive mast cells is decreased in IBS compared with HV, this is not associated with the presence of visceral hypersensitivity or abnormal stress response. Our data question the role of microscopic inflammation as an underlying mechanism of visceral hypersensitivity, but rather suggest dysregulation of the mucosal immune system in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
98
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 66 publications
6
98
1
2
Order By: Relevance
“…Braak et al ( 8 ) also conclude that a decrease in mast cells found might indicate a dysregulation of the immune system. However, it is important to note that mast cell numbers in volunteers were high with a wide range of values.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…Braak et al ( 8 ) also conclude that a decrease in mast cells found might indicate a dysregulation of the immune system. However, it is important to note that mast cell numbers in volunteers were high with a wide range of values.…”
mentioning
confidence: 95%
“…CRH signaling pathways have been shown to have an important role in stress-related alterations of gut function related to intestinal symptoms ( 7 ). Braak et al ( 8 ) have attempted to clarify IBS pathophysiology using these strategies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Th ey also suggest that cysteine as well as serine proteases may be involved in this process -an interesting fi nding given the presence of cysteine proteases in intestinal cells other than mast cells, the dominant source of serine proteases. Th e role of mast cells in IBS has been the subject of considerable interest and, although some have reported increased mast cell numbers and / or activation in IBS ( 22 -25 ), this fi nding has not been universal ( 26,27 ). Th e observation that proteases other than those derived from mast cells could be involved in neuronal eff ects mediated by IBS supernatants is an important one but the possibility that these proteases could be of bacterial origin also needs to be considered ( 28 ).…”
mentioning
confidence: 99%